ANALYSIS OF DOMINANT LAND COVER CLASS BASED ON LAND CHANGE CLUSTER PATTERN IN WEST JAVA PROVINCE - Imanuel S, Christopher
Study of land cover change is important in order to understand the global environment change. Land cover change is specific to certain time, place, scale, and condition. With cluster, it indicates the pattern and concentration of the location of land cover change, so it is possible to plan preventive action right on target. The understanding of land cover dynamics can be enhanced by identifying the dominant land cover change, which will lead to better land cover management. Hence, this study conducted to identify the dominant land cover change in each cluster. There are two steps in performing cluster analysis, spatial pattern analysis and cluster pattern analysis. Spatial pattern analysis (global statistics) provides information on data pattern whether clustered, random, or dispersed. Cluster pattern analysis (local statistics) can identify the cluster locations. After the clusters are identified, the analysis of the dominant land cover change is applied on the clusters. The results show that the dominant land cover change in West Java in 2005-2010 are heterogeneous, with the top three broadest classes changes are rice field to field/ moor (144,662.76 ha), forest to fields/ moor (36,339.84 ha), and fields/ moor to settlement (36,069.39 ha). This study managed to identify 99,94% are the dominant land cover change clusters and 0,06% of the clusters are remained the same class.